PERSPEKTIF HUKUM DALAM PENGAWASAN PENGELOLAAN KEUANGAN DAERAH - Isnawati Isnawati (Universitas 17 Agustus 1945 Samarinda, 2013)
Phenomena occurring in the area are very interesting; given the current state of affairs of the organization of the era is the era of decentralization of government affairs conducted by the local government. Shift in government policy is characterized by the localization policy strengthening the decentralization process that spawned regional autonomy. Good supervision in the planning stages of the budget, to be followed by good supervision in the area of financial management steps next stages of implementation and utilization of APBD. In every stage of regional financial management, strategic aspects of the monitoring in implementing are the principles of the net. Corruption in the use of the budget cannot be separated from the process of planning budgeting which is simply the process of preparing the RAPBD, often irregularities in the planning process marred practices are not good, among others, the project deposit, money politics so that the implementation of the APBD will also loaded with various irregularities.